Efficient piezocatalytic properties of Na0.5Bi0.5TiO3 nanoparticles for dye degradation and hydrogen peroxide production - Bocheng Liang; Xiaoting Zhu; Haimiao Yu; Yongcheng Zhang; Wanneng Ye (Journal of Advanced Dielectrics)
Piezocatalysis has emerged as a promising environmental remediation technique, and the exploration of environmentally friendly and high-performance piezocatalysts is crucial for their practical applications. In this work, the bismuth sodium titanate (Na[Formula: see text]Bi[Formula: see text]TiO3 (NBT)) exhibited efficient piezocatalytic activity toward typical organic pollutants degradation, including acid orange 7, methylene blue, rhodamine B and methyl orange. Notably, rhodamine B was degraded by 98.1% within 30[Formula: see text]min with a reaction rate constant of 0.130[Formula: see text]min[Formula: see text]. Furthermore, the NBT achieved a hydrogen peroxide production efficiency of 538[Formula: see text][Formula: see text]mol/g⋅h without the sacrificial agent, indicating that the NBT is a superior piezocatalyst for dye degradation and hydrogen peroxide generation. This work demonstrated that by using mechanical energy, the NBT can be used for degrading organic pollutants in wastewater and hydrogen peroxide generation.